The Who in VR/AR for Education: A Scoping Review from IEEE Publications - Arbana Kadriu; Lejla Abazi Bexheti (ENTRENOVA - ENTerprise REsearch InNOVAtion, 2022)
HEIs have continuously been the vanguard of novel technologies, pushing progress and establishing the afterward generation of scientists, businesspersons, and engineers. Virtual and augmented reality technologies are on the borderline of enlargement nowadays. To better understand who are essential actors in this new research area, we have extracted metadata of all published papers by IEEE, dating from 1990 to 2021, using keywords VR, AR, and Education. For each publication, we have extracted the list of all the authors, creating a co-authorship dataset. This dataset is then further processed using social network analysis metrics. The results are discussed to understand research publications' main actors driving VR/AR/Education trends.
Keywords: C00; C30; 330; Virtual Reality; Augmented reality; Teaching; Education